Champlain Sea Foraminifera and Ostracoda: a systematic and paleoecological synthesis - Cronin, Thomas (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Champlain Sea deposits from Québec, Ontario and the United States yielded over 40 ostracode and 60 benthonic foraminiferal species. Geographical trends in foraminiferal species diversity as measured by the Shannon-Wiener Information Function, H(S), show highest diversities (H(S) = 1.6-1.7) in the western Champlain Sea of Ontario, southern Québec and near Québec City, while a significantly less diverse fauna (H(S) = 1.0) inhabited the Champlain Valley. Three environmentally distinct phases of the sea based on ostracode species distribution were recognized in the Champlain Valley and southern Québec An early period, characterized by fresh water and euryhaline marine species, represents a lacustrine-marine transition. Subsequently, frigid to subfrigid, polyhaline to euhaline conditions prevailed. Finally, some time between 11,000 and 10,600 yr BP a salinity decrease and a water temperature increase is inferred from the dominance of mesohaline, cold temperate ostracode species. Additional evidence for temporal salinity variation are mean foraminiferal species diversity values which are 1.0, 1.5 and 1.2 respectively for the three phases.